1993
DOI: 10.1182/blood.v82.9.2865.2865
|View full text |Cite
|
Sign up to set email alerts
|

New insights suggesting a possible role of a heat shock protein 70-kD family-related protein in antigen processing/presentation phenomenon in humans

Abstract: A possible role of the peptide binding protein (PBP) 72/74 in antigen processing and presentation has been recently suggested in mice. In order to evaluate a possible analogous role of a PBP72/74-related protein in humans, immunoelectron microscope investigations, functional studies, and immunofluorescence analyses were performed on normal human peripheral antigen-presenting cells. We demonstrated that the determinant recognized by antiheat shock protein (HSP) 72/73 monoclonal antibody (MoAb) is constitutively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In addition, we saw limited cytoplasmic uptake by two monocytic cell lines, THP-1 and U937, but only after extended (6-24 h) incubation with high concentrations (100 μg/ml) of Hsp70-FITC (data not shown). The B cell-and monocyte-specific Hsp70 transport activity we describe is consistent with reports which propose a role for Hsp70 heat shock family members in antigen presentation (Vanbuskirk et al, 1989;Manara et al, 1993), as these cells are generally considered to function as antigen-presenting cells. The cell-type specificity and inducibility of cellular Hsp70 uptake may reflect differential expression of a required surface or nuclear receptor for the Hsp70 protein.…”
Section: Resultssupporting
confidence: 90%
“…In addition, we saw limited cytoplasmic uptake by two monocytic cell lines, THP-1 and U937, but only after extended (6-24 h) incubation with high concentrations (100 μg/ml) of Hsp70-FITC (data not shown). The B cell-and monocyte-specific Hsp70 transport activity we describe is consistent with reports which propose a role for Hsp70 heat shock family members in antigen presentation (Vanbuskirk et al, 1989;Manara et al, 1993), as these cells are generally considered to function as antigen-presenting cells. The cell-type specificity and inducibility of cellular Hsp70 uptake may reflect differential expression of a required surface or nuclear receptor for the Hsp70 protein.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, normal human resting antigen-presenting cells express a determinant that is part of the human PBP72/74 homologue on their cell surface. These data and the ability of an anti-hsp72/73 monoclonal antibodies to consistently inhibit the antigen-presenting/ accessory cell functions of human monocytes suggest that human PBP72/74 homologue plays an important role in antigen presentation in the human immune system [31].…”
Section: Discussionmentioning
confidence: 77%
“…It is expressed on the cell surface of B cells, as well as on macrophages in mice [53]. Also in humans, the majority of CD14 positive monocytes coexpress the determinant recognized by anti-hsp72/73 monoclonal antibody [31]. Moreover, normal human resting antigen-presenting cells express a determinant that is part of the human PBP72/74 homologue on their cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their maintenance of normal protein structure, heat shock proteins have been implicated in the development of certain immune responses, including the development of autoimmune diseases [22]. Indeed, it has been suggested that the 70-kD family may play a role in antigen processing and presentation [23].…”
Section: Discussionmentioning
confidence: 99%